If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + -9 = 13x + 51 Reorder the terms: -9 + 14x = 13x + 51 Reorder the terms: -9 + 14x = 51 + 13x Solving -9 + 14x = 51 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -9 + 14x + -13x = 51 + 13x + -13x Combine like terms: 14x + -13x = 1x -9 + 1x = 51 + 13x + -13x Combine like terms: 13x + -13x = 0 -9 + 1x = 51 + 0 -9 + 1x = 51 Add '9' to each side of the equation. -9 + 9 + 1x = 51 + 9 Combine like terms: -9 + 9 = 0 0 + 1x = 51 + 9 1x = 51 + 9 Combine like terms: 51 + 9 = 60 1x = 60 Divide each side by '1'. x = 60 Simplifying x = 60
| 3/x-2=1/x | | 4/56 | | 3(4x+5y)=12 | | sqrt(x^2-3x)=2 | | -6+7(x-3)=37-x | | .08(x)+.12(x+250)=348 | | x+0.13x=3500 | | X^2-18x-31=0 | | 28=4/3w | | -7(-5k-8)=196 | | 24/0.3 | | 2f+3w=15.55 | | -272=3n-7(8n+1) | | 0.7z-3=0 | | 3.5+46.9*x-9.8*x^2=0 | | 6+3x=8+11 | | 1404=.02(x) | | 14M-28=4(M+3) | | 3y=28-4y | | X/3=x-31/2 | | (3x^5-2x^3+4)+(x^4+2x^3-7)= | | 2y-2/5=-1/3 | | 8(3a+6)=9(2a-3)-9 | | 5-(2x+4)=15 | | -8(-x-7)=-x+29 | | 24y-20x=72 | | 1404=.08(x)+.04(y) | | 4(x+1)=2(x+3)-4 | | Z^2=8+6i | | 11-w=187 | | 4x+1=3(x+2)+2x | | 20.44=1.5x*x |